Efektifitas Pemberian Stimulant Better dan Waktu Sadap Terhadap Produksi Lateks Tanaman Karet (Hevea brasiliensis Muell Arg - Engelbertus Huvat; Akhmad Sopian; Tutik Nugrahini; Zainudin Zainudin (Universitas Widya Gama Mahakam, 2018)
The factors that influence rubber production are planted clones, plant care and tapping techniques. With the right tapping technique, both tapping time, tapping method and mature tapping age, the production potential of a superior clone of rubber plants that has been well maintained can be maintained. The technique of rubber tapping is closely related to the expected level of production, even very determining the age of the tree economy. The research objective was to determine the effect of stimulant better and tapping time on latex production. The method used was a randomized block design with two-factor split plot design. The first factor (main plot) is the time of tapping consists of 3 levels, namely; w1: 05 in the morning, w2: 06 in the morning, w3: 07 in the morning. The second factor (sub-plot), namely the stimulant dosage better consists of 4 levels, namely; b0: control, b1; 0.5 g, b2; : 1 g, b3; 1.5 g. The results showed that stimulate better treatment had a significant effect on latex volume, wet weight and latex dry weight, but was not significant for latex dryness levels. Tapping time was not significant for latex yield, latex volume, wet weight, latex dry weight and highest dry rubber content at 7am. Stimulant Better treatment has a significant effect on latex volume, wet weight, and latex dry weight, but if given at high doses it will reduce the dry content of rubber. The interaction of treatment when tapping and stimulant is better not significant for latex production. The stimulant application better does not exceed the dose of 0.5 g / principal. Doses> 0.5 g / staple will have an impact on the dry tapping field.